THE ROLE OF INTERACTIVE METHODS IN DEVELOPING STUDENTS’ CRITICAL AND CREATIVE THINKING - Kodirova Ferangiz Himmatillo qizi (Bright Mind Publishing, 2025)
The 21st century demands education systems that go beyond rote memorization and foster higher-order thinking skills among learners. This study explores the role of interactive teaching methods in developing students’ critical and creative thinking skills. Interactive methods—such as collaborative learning, problem-based learning, inquiry activities, and digital simulations—actively engage students in the learning process and encourage them to analyze, evaluate, and generate new ideas. The research highlights that when students participate in interactive environments, they demonstrate improved analytical reasoning, originality, and flexibility in problem-solving. Using a mixed-method approach that combines quantitative analysis of student performance and qualitative observation of classroom dynamics, the study finds a statistically significant enhancement in both critical and creative thinking skills among students exposed to interactive pedagogies compared to those taught through traditional methods. The findings suggest that effective implementation of interactive strategies, supported by teacher facilitation and a positive classroom climate, can transform learning into an active, reflective, and innovative process. The study concludes with recommendations for educators and policymakers to integrate interactive methods systematically into curricula to nurture creative and critical thinkers equipped for lifelong learning.
Keywords: Interactive methods, critical thinking, creative thinking, collaborative learning, problem-based learning, digital pedagogy, student engagement, active learning, pedagogical technologies, inquiry-based learning.